Porous yolk–shell microspheres as N–doped carbon matrix for motivating the oxygen reduction activity of oxygen evolution oriented materials. (16th August 2017) - Zhou, Jinqiu; Wang, Mengfan; Qian, Tao; Liu, Sisi; Cao, Xuecheng; Yang, Tingzhou; Yang, Ruizhi; Yan, Chenglin
Abstract: It is highly challenging to explore high–performance bi-functional oxygen electrode catalysts for their practical application in next-generation energy storage and conversion devices. In this work, we synthesize hierarchical N–doped carbon microspheres with porous yolk–shell structure (NCYS) as a metal-free electrocatalyst toward efficient oxygen reduction through a template-free route. The enhanced oxygen reduction performances in both alkaline and acid media profit well from the porous yolk–shell structure as well as abundant nitrogen functional groups. Furthermore, such yolk–shell microspheres can be used as precursor materials to motivate the oxygen reduction activity of oxygen evolution oriented materials to obtain a desirable bi-functional electrocatalyst. To verify its practical utility, Zn–air battery tests are conducted and exhibit satisfactory performance, indicating that this constructed concept for preparation of bi-functional catalyst will afford a promising strategy for exploring novel metal–air battery electrocatalysts.